Avidity of specific IgG antibodies elicited by immunisation against Haemophilus influenzae type b. Issue 3 (March 1995) - Agbarakwe, A E; Griffiths, H; Begg, N; Chapel, H M
Abstract : AIM–To investigate the avidity of specific IgG polyribosyl ribitol phosphate (PRP) antibodies induced by three Haemophilus influenzae type b (Hib) conjugate vaccines: PRP-meningococcal outer membrane protein complex (PRP-OMP), PRP-non-toxic mutant diphtheria toxin, CRM197 (HbOC) and PRP-tetanus toxoid (PRP-T). METHODS–One hundred and ten infants were immunised with one of the vaccines at two, three and four months of age. Blood samples were taken after each vaccination and serum stored at -20 degrees C. Serum samples collected after the third course (that is, at five months of age) were submitted to antibody avidity assessment, using a urea enzyme linked immunosorbent assay (ELISA). RESULTS–All three conjugate vaccines elicited IgG PRP antibodies of high median avidity. The resultant antibody populations were heterogeneous with regard to avidity, which in turn was independent of PRP antibody concentration. CONCLUSIONS–With the recent findings of a correlation between bactericidal killing and affinity, our data highlight the need for a protective level to be expressed qualitatively as well as quantitatively.